Biodegradation Study of Biomaterials Composed of Acrylated Epoxidized Soybean Oil: An In Vitro Study. - Sibilia, Diego; Amendolea, Martina; Sangiovanni, Roberta; Bragaglia, Mario; Nicoletti, Fabrizio; Filetici, Pierfrancesco; D'Addona, Antonio; Nanni, Francesca; Dassatti, Leonardo; Nocca, Giuseppina; Silva, Edilene O. (BioMed Research International, 2024)
In the field of regenerative medicine, acrylated epoxidized vegetable oils are emerging as a promising avenue of exploration. The aim of this study is to evaluate the degradability of two formulations of acrylated epoxidized soybean oil (AESO): pure AESO and AESO diluted with soybean oil (SO) for potential bioprintability applications. The comprehensive investigation of these two polymeric formulations included optimization of polymerization conditions, confirmation of cytocompatibility, and, most importantly, the study of their degradability. The results reveal that AESO, used as a biomaterial for biomedical applications, undergoes a distinctive degradation process, combining both enzymatic and oxidative degradation (AESO/SO samples lose 29.45% of their weight after 60 days). This phenomenon is the result of a complex interplay of factors, including the chemical composition and physical characteristics of the polymer, the unique tissue environment in which it is implanted, and the duration of implantation.